Angioembolisation of Cremasteric Artery for Scrotal Haematoma Following Hernial Repair - Audrey Lee Sook Fang; Zakhirati Zainol Abidin; Dhayal Balakrishnan; Muhammad Safwan Norizan (The Interventionalist Journal, 2024)
Cremasteric artery is a branch of inferior epigastric artery supplying the cremaster muscle and coverings of the cord. The possible consequence of injury to this artery is scrotal haematoma. We present a case of haemorrhage from unexpected cresmastric artery injury post-hernioplasty treated with angioembolisation. To the best of our knowledge, this has not been reported in literature. A 66-year-old gentleman with left indirect inguinal hernia underwent a left inguinal hernioplasty in our institution with no immediate complications. However he presented to the emergency department the day after the procedure with complaints of rapidly worsening painful left scrotal swelling accompanied with symptoms of intestinal obstruction. Emergency laparotomy and re-do left hernioplasty was performed, revealing a strangulated inguinoscrotal hernia. Post-operatively, there was non-resolving scrotal swelling with a drop in the haemoglobin level; from 11.9g/dl to 8.5g/dl requiring packed cell transfusion. CT angiogram revealed active contrast extravasation from the left cremasteric artery. Angiographic run confirmed the finding and the left cresmatric artery was superselectively cannulated with a 1.9Fr microcatheter and embolization done with 0.5mm microcoil. Ultrasound scan 24-hour post-procedure showed patent proximal vessel. Clinically there was a reduction of the left scrotal swelling and the haemoglobin remained stable. Cremasteric artery courses laterally deep into the fascia transversalis entering the cord deep to the internal spermatic fascia to supply the cremaster muscle and coverings of the cord. This course renders the artery to be prone for injury during procedure such as hernioplasty; one of the possible consequences is scrotal haematoma. This artery is usually small in caliber and its identification is important for efficient and effective treatment. Angioembolisation is able to treat this injury with superior precision owing to its ability for localization and selective cannulation of the offending vessel.